(3QSGdI aj MOhO GdCdaGX GdeSJYedI YfO GdabgGAs
(3ChdgG (B:s
(3HGH HjGf cTa GdCdaGX GdeSJYedI GdJi JLQi Ydi CdSf GdabgGA ai Gdabg MJi dG jLQi ajgG GdSgh hGdZdW , dCf CMcGe GdTQY eHjfI Ydi gPg GdCdaGX HjGf GdMO (B: (3GdMO gh GdefY dZI , hefg Sei s
(3BNQgG (B:s
(3hGdfgi(B: (3WdH GdGeJfGY Yf GdaYd GdNHQ fhYGf eQSd heSfO , aGdeQSd efg eG CQSdg GdQGhi EQSGdkG ef ZjQ ESfGO Edi QGh BNQ , hgh MLI YfOfG Ke GdeSfO eG CSfOg GdQGhi Edi QGh BNQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GddZIs